Short Fibre Reinforced Cementitious Composites and Ceramics - Herrmann, Heiko; Schnell, Jürgen (Advanced Structured Materials,, 2019)
This volume shines a new light on short fibre reinfoced cementitious composites and particle reinforced ceramics. It offers insight from various disciplines like civil engineering, material sciences and micro-mechanics, and collects 9 experimental, numerical and theoretical studies written by top researchers in composite concrete science. The book presents the outcome of the EUROMECH 582 colloquium "Short Fibre Reinfoced Cementitious Composites and Ceramics" held 20 - 22 March 2017, Tallinn, Estonia. .